2014
DOI: 10.1002/smll.201401707
|View full text |Cite
|
Sign up to set email alerts
|

Functional Nanomaterials Can Optimize the Efficacy of Vaccines

Abstract: Nanoscale materials can improve the efficacy of vaccines. Herein we review latest developments that use nanomaterials for vaccines. By highlighting the relationships between the nanoscale physicochemical characteristics and working mechanisms of nanomaterials, this paper shows the current status of the developments where researchers employ functional nanomaterials as vector and/or immunoregulators for vaccines. It also provides us some clues for improving the design and application of nanomaterials to optimize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 140 publications
0
34
0
Order By: Relevance
“…This review allows chemists, materials scientists, and biologists to think about AuNPs from a surface chemistry Vaccination is one of the most effective and low-cost means to prevent and control human diseases such as Zika virus, hepatitis B virus (HBV) and inuenza virus. [15][16][17] Most of the vaccines consist of an antigen, a vector and adjuvants. The efficiency of a vaccine is highly dependent on the vector effect.…”
Section: Introductionmentioning
confidence: 99%
“…This review allows chemists, materials scientists, and biologists to think about AuNPs from a surface chemistry Vaccination is one of the most effective and low-cost means to prevent and control human diseases such as Zika virus, hepatitis B virus (HBV) and inuenza virus. [15][16][17] Most of the vaccines consist of an antigen, a vector and adjuvants. The efficiency of a vaccine is highly dependent on the vector effect.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, several shortcomings, especially short‐lived and weak immune responses still limit their applications . Recently, the combination of biotechnology and chemistry of nanomaterials has enabled the further development of subunit vaccines . Nanoparticulate delivery systems afford benefits for vaccines in many aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the effects of antigen carrier size and shape have also been investigated as the size and shape of nanoparticles affect both nanoparticle uptake [23][24][25][26][27][28][29][30][31][32] and immune responses. [33][34][35][36][37][38][39] Plebanski et al reported that the size of the antigen carrier inuenced the immune response pathway in vivo aer intradermal immunization. 33 We previously demonstrated the effects of the shape of the antigen scaffold on vaccine efficacy and cytokine production in mice immunized intraperitoneally.…”
Section: Introductionmentioning
confidence: 99%